Analysis of The Influence of Ease of Use, Financial Literacy, and Risk Tolerance on Investment Decisions in The Ajaib Application - Sila Prasada; Aris Sunindyo Arif Mursito; Teguh Budi Santosa (Applied Accounting and Management Review (AAMAR), 2025)
This study aims to examine the extent to which convenience, financial literacy, and risk tolerance influence investment decisions on the Ajaib investment application. The data were collected using a non-probability sampling method with a purposive sampling technique, involving 100 university students who are active users of the Ajaib application. The analytical method employed in this research is multiple linear regression, supported by the F-test, coefficient of determination test (Adjusted R²), and t-test. The results indicate that the variables of ease of use, financial literacy, and risk tolerance have a significant simultaneous influence on investment decisions on the Ajaib application. Furthermore, each variable also shows a significant partial influence on investment decisions.